Bi-Univalent Function Classes Defined by Using a Second Einstein Function. (20th April 2022) - El-Qadeem, Alaa H.; Saleh, Saleh A.; Mamon, Mohamed A.
Abstract : Motivated by q-calculus, subordination principle, and the second Einstein function, we define two families of bi-univalent analytic functions on the open unit disc of the complex plane. We deduce estimates for the first two Maclaurin's coefficients and the Fekete-Sezgö functional inequalities for the functions that belong to these families of functions.